Relationship between Body Mass Index and Gender with Asthma - Dewi Puji Ayuningrum; Risna Nur Fajariyah; Randy Novirsa; Erni Astutik (Jurnal Berkala Epidemiologi, 2021)
Background: Asthma is ranked 16th among the leading causes of years lived with disability (YLD) and ranks 28th among the causes of global burden of disease (GBD). Various potential factors can cause asthma, which include body mass index (BMI) and gender. Purpose: This research aimed to determine the relationship between BMI and gender in people living with asthma in Indonesia. Methods: This research employed secondary data obtained from the Indonesian family life support (IFLS) 5th edition. This research used an observational analysis technique with a cross-sectional approach. The number of respondents in this research were 30,713. In this study, the BMI category was based on WHO’s classification for Asians. Data was analyzed using logistic regression tests and chi square. Statistical significance was set at a value of p<0.05. Results: As many as 17,175 respondents had a normal BMI range (56.92%), out of which the majority were women—16,001 respondents (52.10%). After controlling the other variables, statistical test results with logistic regression indicated that male respondents had 1.23 times the odds of experiencing asthma compared to females (adjusted odds ratio (AOR)=1.23; 95% confidence interval (CI), 1.04–1.44; p=0.02). Again, after controlling the other variables, underweight respondents had 1.31 times the odds of experiencing asthma compared to respondents who had a normal BMI (AOR=1.31; 95%CI=1.07–1.59; p=0.01). Conclusion: A relationship between gender and the category of people who were underweight after determining their BMI could be established. Health counseling can be provided to help improve the respiratory conditions of these individuals.